2008
DOI: 10.2188/jea.je2006332
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Serum Uric Acid among Ex-smokers

Abstract: Background: It remains unclear whether serum uric acid level increases after the cessation of smoking. Methods: In 2000, we conducted a cross-sectional study on the effects of smoking cessation on serum uric acid levels by analyzing the results of annual health check-ups in the Japanese male working population (n = 16,642). Results: The serum uric acid level (6.18 mg/dL) was the highest in ex-smokers, followed by that in never-smokers (6.10 mg/dL) and that in current smokers (5.98 mg/dL). Ex-smokers weighed 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 5 publications
2
15
1
Order By: Relevance
“…10 , 47 It has been suggested that smoking may suppress uric acid levels via the action of the superoxides found in cigarette smoke. 16 Given that the effects Total non-occupational physical activity, which included leisure time, daily living, and commuting-related physical activity, was inversely related to the prevalence of hyperuricemia ( Table 3 ). The ORs for ≤3, >3-6, >6-9, >9-12, and >12 non-occupational METs were 1.00, 0.80, 0.73, 0.75, and 0.57 ( P < 0.001), respectively, in fully adjusted analyses (including BMI and WHR), showing a dose-response relationship.…”
Section: Resultsmentioning
confidence: 99%
“…10 , 47 It has been suggested that smoking may suppress uric acid levels via the action of the superoxides found in cigarette smoke. 16 Given that the effects Total non-occupational physical activity, which included leisure time, daily living, and commuting-related physical activity, was inversely related to the prevalence of hyperuricemia ( Table 3 ). The ORs for ≤3, >3-6, >6-9, >9-12, and >12 non-occupational METs were 1.00, 0.80, 0.73, 0.75, and 0.57 ( P < 0.001), respectively, in fully adjusted analyses (including BMI and WHR), showing a dose-response relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the possible impact of these effects, all patients with diabetes were excluded from the analysis. Although increased levels of SUA among ex-smokers have been previously described [36], an acceptable explanation of this phenomenon has not yet been found. Although several studies [37,38] have partly explained the cardiovascular benefit of the uricosuric effect from fenofibrate, losartan and atorvastatin, our patients were recruited before the losartan and atorvastatin era and, therefore, only a small number of patients (13%) were treated with ACEIs while none were treated with statins.…”
Section: Discussionmentioning
confidence: 99%
“…Its serum levels (SUA), governed by the production (liver) and elimination (mainly the kidney) rates, are influenced by genetically determined factors (eg, activity of synthesizing enzymes or renal transporter systems), racial and demographic characteristics (eg, sex, gonadal function in women, obesity), diet (eg, purine-rich foods, fructose, alcohol), habits (eg, SUA is lower in smokers and increases after quitting), morbidity (eg, heart or renal failure, malignancies), and medications (eg, diuretics, cytotoxic agents) (1)(2)(3)(4). The role of SUA in cardiovascular and renal diseases has been intensively investigated, although not without controversy (5).…”
mentioning
confidence: 99%